Standards for thermal comfort indoor air temperature standards for the 21st century - Nicol, Fergus 1940-; Humphreys, Michael; Sykes, Oliver; Roaf, Susan (Chapman & Hall, 1995)
Standards for Thermal Comfort brings together contributions from around the world, reflecting new approaches to the setting of standards which can apply to all climates and cultures.